Recent Epidemiology of Nonalcoholic Fatty Liver Disease - Murag, Soumya; Ahmed, Aijaz; Kim, Donghee (Gut and liver, 2021)
The ongoing obesity epidemic and the increasing recognition of metabolic syndrome have contributed to the growing prevalence of nonalcoholic fatty liver disease (NAFLD), the most common form of liver disease worldwide. It is imperative to understand the incidence and prevalence of NAFLD as it is associated with a profound economic burden of hospitalizations, including the shifting trends in liver transplantation. The long-term cumulative healthcare cost of NAFLD patients has been shown to be 80% higher than that of non-NAFLD patients. We explore diagnostic challenges in identifying those with NAFLD who have a higher predilection to progress to end-stage liver disease. We aim to assess all-cause and cause-specific mortality as it relates to NAFLD.